The Dance of Week-End Return and Volume: A Symphony - Asnawi, Said Kelana; Pangestu, Windy; Widjaja, Caroline (Jurnal Nusantara Aplikasi Manajemen Bisnis, 2024)
Abstract The weekend effect study is one of the studies relating to market anomalies. Research on market anomalies is important because it can be a guide for investors to transact. Concerning transactions, the TV-return pair is an appropriate indicator compared to the return itself. We use various combinations of TV-Return to find the weekend effect. The results show that mostly there is no weekend effect. Thus the efficient market hypothesis applies. This result can be a reference for investment, where Friday or Monday is no different. Investors can't beat the market